A svet je kroženje in povezava zagonetna … : zbornik ob 80-letnici zaslužnega profesorja dr. Mirka Križmana = Festschrift für Prof. em. Dr. Mirko Križman zum 80. Geburtstag (University of Maribor Press, 2012)
But the World is Circling and the Link is Mysterious ... : Proceedings of the 80th Anniversary of the Emeritus Professor dr. Mirko Križman. Honorable prof. dr. Mirko Križman (1932, Zgornja Ponikva) graduated in German and Slovenian with a degree in literature from the University of Ljubljana, a master’s degree in German literature and stylistics from the University of Zagreb and a doctoral dissertation on Christine Lavant from the Faculty of Arts, University of Ljubljana. From 1984 until his retirement he worked as a full professor of German language and stylistics at the Faculty of Education, now the Faculty of Arts, University of Maribor. During many years of his professional academic work, he indispensably co-authored undergraduate and graduate German studies at the University of Maribor; under his tutelage, a considerable number of students of German language and literature completed their studies. He received the Boris Kidric Fund Award for excellence in scientific work, the Faculty of Education and the University of Maribor awarded him with a gold plaque and the title of deserving professor, the City of Maribor with a silver coat of arms, the Union of Cultural Organizations in Maribor with a Gold badge. Since 2001 he is an honorary member of the Association of University Professors Maribor. He has twice served as chairman of the National Commission for the Prešeren Award for Literature. He has lectured at numerous scientific events at home and around the world, and is a member of the International Union for Germanic Linguistics and Literary Sciences.